Insuficiencia renal aguda. - MIYAHIRA ARAKAKI, Juan Manuel (2013)
Acute renal failure (ARF) is a clinic syndrome characterized by decline in renal function occurring over a short time period. Is a relatively common complication in hospitalized critically ill patients and is associated with high morbidity and mortality. ARF has often a multi-factorial etiology syndrome usually approached diagnostically as pre-renal, post-renal, or intrinsic ARF. Most intrinsic ARF is caused by ischemia or nephrotoxins and is classically associated with acute tubular necrosis (ATN). High mortality is associated with severity of ARF, age more than 60 years old and presence of pulmonar and cardiovascular complications. Most patients who survive an episode of ARF recover sufficient renal function; however, 50% have subclinical functional defects in renal function or scarring on renal biopsy. ARF is irreversible in approximately 5% of patients, usually as a consequence of complete cortical necrosis.